Úprava sériově vyráběného spalovacího motoru na motor pro závodní použití - Závodný, Tomáš (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2015)
Tato bakalářská práce rozebírá úpravu motoru pro závodní použití do autokrosu. První část práce je pojata jako rešeršní a je zaměřená na to proč byl tento motor upravován a dále jaké úpravy byly provedeny. Další část se věnuje provedení simulace v softwaru ADAMS MD R3. Výsledky těchto simulací byly dále zpracovány a vyhodnoceny. Závěr obsahuje srovnání výsledků ze softwaru s výsledky ze skutečné motorové brzdy, a zhodnocuje celkový úspěch tohoto projektu v reálném životě.

This bachelor’s thesis analyses the modification of the serially produced combustion engine to get an engine for racing purposes. The first part is conceived as searching and is focused on why this serially produced engine was modified to racing engine and which adjustments were made on this naturally aspirated engine. Another part was dedicated to design simulation in the software ADAMS MD R3 and the results of these simulations were processed and evaluated. Conclusion contains a comparison of the results from the software and results from an actual engine dynamometer, and what is the overall success of the project in real life.
Adjustment and modification made to the serially produced combustion engine to get an engine for racing purposes
Keywords: Autokros; úprava spalovacího motoru; Xbuggy; atmosferický motor; ADAMS; MBS; Autocross; modification of combustion engine; Xbuggy; naturally aspirated engine; ADAMS; MBS